2012
DOI: 10.12693/aphyspola.121.284
|View full text |Cite
|
Sign up to set email alerts
|

Models for the Analysis of IR Reflectivity in TlBiTe2with Different Size of Twins

Abstract: In this work TlBiTe 2 were grown by a modified Bridgman technique and examined samples had different lateral dimensions of twins, ranging from 0.1 µm to 1 µm. The average lateral size of the twins seems to affect free carrier concentration and plasma frequency. Infrared spectra were analyzed by two models, the extended Drude model and a generalized empirical model of frequency-dependent damping factor. Increase in size of twins affects the electronic properties and hence plasma reflectivity and free carrier co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…1,[7][8][9] Different crystals belong to the interesting group A III B V X 2 VI of layer and chain semiconductors, which have attracted the attention of researchers due to their special structural, electrical and thermo-electrical properties. [10][11][12][13][14][15][16][17][18] Many amorphous semiconductors especially chalcogenide glasses exhibit an abrupt change in electrical resistivity when subjected to an adequately high electric field. In recent years, it has been observed that the switching effect is not only characteristic of these kind of materials but is also present in many crystalline materials, like binary semiconductor and ternary chalcogenide semiconductor compounds such as TlGaTe 2 , TlInSe 2 , TlInTe 2 and InGaSe 2 .…”
Section: Introductionmentioning
confidence: 99%
“…1,[7][8][9] Different crystals belong to the interesting group A III B V X 2 VI of layer and chain semiconductors, which have attracted the attention of researchers due to their special structural, electrical and thermo-electrical properties. [10][11][12][13][14][15][16][17][18] Many amorphous semiconductors especially chalcogenide glasses exhibit an abrupt change in electrical resistivity when subjected to an adequately high electric field. In recent years, it has been observed that the switching effect is not only characteristic of these kind of materials but is also present in many crystalline materials, like binary semiconductor and ternary chalcogenide semiconductor compounds such as TlGaTe 2 , TlInSe 2 , TlInTe 2 and InGaSe 2 .…”
Section: Introductionmentioning
confidence: 99%